1996
DOI: 10.1016/0925-4439(96)00019-1
|View full text |Cite
|
Sign up to set email alerts
|

Lung collagen cross-links in rats with experimentally induced pulmonary fibrosis

Abstract: Rats were intratracheally instilled with bleomycin or with silica (quartz) dust to induce lung fibrosis. Several weeks later, purified collagen chains (or collagen digests) were isolated from the lungs of these animals and from age-matched controls instilled intratracheally with saline solution, and the ratios of hydroxylysine to lysine and of the dysfunctional cross-links DHLNL to HLNL were quantified. Collagen from fibrotic lungs had significantly higher ratios of DHLNL:HLNL than did control lungs, 15.5 +/- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Concerning the ECM cross-link status of mouse lungs following hyperoxia exposure, the abundance of the DHLNL collagen cross-link, as well as the DHLNL/HLNL, was increased in lungs from hyperoxia-exposed mice, suggestive of a profibrotic state (17,63). The application of BAPN concomitantly with hyperoxia blunted this increase in lung collagen accumulation and partially normalized the DHLNL/HLNL.…”
Section: Discussionmentioning
confidence: 95%
“…Concerning the ECM cross-link status of mouse lungs following hyperoxia exposure, the abundance of the DHLNL collagen cross-link, as well as the DHLNL/HLNL, was increased in lungs from hyperoxia-exposed mice, suggestive of a profibrotic state (17,63). The application of BAPN concomitantly with hyperoxia blunted this increase in lung collagen accumulation and partially normalized the DHLNL/HLNL.…”
Section: Discussionmentioning
confidence: 95%
“…Lysyl oxidase expression and the proportion of hydroxylated lysine residues are increased in fibrotic states (104). An increase in cross-linking and altered cross-linking patterns have been implicated in dermal fibrosis (17), in ARDS in the lung (86), in myocardial fibrosis (98), and in pulmonary fibrosis (56,142). A recent study demonstrated that inhibition of lysyl oxidase-like-2 prevented the development of bleomycin-induced lung fibrosis and reversed established fibrosis (6).…”
Section: Collagen Structure and Composition In Areas Of Fibrosismentioning
confidence: 99%
“…What is unclear from this technique is whether all collagen in the lung is degraded at similar rates or whether there are pools of collagen that are more or less accessible to degradation (55,58,90). It has been suggested that the increased ratio of more stable dihydroxylysinonorleucine cross-links to less stable hydroxylysinonorleucine crosslinks found in fibrotic lung tissue may protect "fibrotic collagen" from enzymatic degradation or mechanical damage (56). Further studies examining whether collagen that is incorporated into fibrillar scar is less prone to degradation than collagen that is part of normal tissue architecture are warranted.…”
Section: Collagen Turnover In the Lungmentioning
confidence: 99%
“…Despite the large differences in lysyl hydroxylation of the telopeptides of collagen type I between skin and bone, for instance, less marked differences are seen in the hydroxylation of lysine residues in the triple helical part of the collagen molecule. To explain this difference, it has been proposed that two forms of LH exist: one that specifically hydroxylates Lys in the ␣-helix (we propose the term ''helical lysyl hydroxylase,'' HLH), and another capable of hydroxylating Lys residues in the telopeptides (telopeptide lysyl hydroxylase, TLH) (16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%